Writing and publishing as conversation/ la escritura y la publicación como conversación/ a escrita e a publicação como conversação (2012)
This article asserts that the publishing process will be better understood as a conversational task that connects empirical precedents and theoretical debates in a given domain to produce new claims. It proposes that the lack of a conversational focus on the current academic environment and an excessive emphasis on impact indexes have created a citational inflation, in which authors and journals try to artificially increase the impact indexes without contributing to disciplinary progress. Based on current literature in psychology and conversational analysis, the article suggests that conversations are collaborative efforts that, in the case of publishing, must respond to two principles: quantity and quality. Quantity refers to making contributions as informative as possible, and quality refers to providing strong support for every claim. To explain this perspective, the author presents two case studies regarding the elaboration of seminal papers on educational psychology and education.